Legal Protection for Minors Victims of Sexual Harassment or Rape at the Sukoharjo Police Department - Iqbal, Muhammad; Junaidi, Amir; Zakaria, Hafid (IHSA Institute, 2025)
Children are God's creations that must be protected by each because of their limitations, one of which is legal protection for children to receive some kind of violence. Receiving child violence has a negative impact on the child's future. I wrote this to determine the need for legal protection for child victims of sexual abuse in accordance with applicable legal regulations. Therefore, the state provides legal protection, all children are bound by law Law Number 31 of 2014 concerning amendments to Law Number 13 of 2006 concerning the protection of children and victims Number 35 of 2014 to prevent violence and abuse against children